2016
DOI: 10.1002/2016ja022404
|View full text |Cite
|
Sign up to set email alerts
|

Off‐great‐circle paths in transequatorial propagation: 2. Nonmagnetic‐field‐aligned reflections

Abstract: There is considerable evidence that plasma structure in nighttime equatorial F layer develops from large‐scale wave structure (LSWS) in bottomside F layer. However, crucial details of how this process proceeds, from LSWS to equatorial plasma bubbles (EPBs), remain to be sorted out. A major obstacle to success is the paucity of measurements that provide a space‐time description of the bottomside F layer over a broad geographical region. The transequatorial propagation (TEP) experiment is one of few methods that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…6. There is mounting evidence that EPBs develop where there are pre-existing upwellings (LSWS) [e.g., Tsunoda and White (1981); Kelley et al (1981); Singh et al (1997); Eccles (2004); Fukao et al (2006); Thampi et al (2009); Tsunoda et al (2011Tsunoda et al ( , 2016aTsunoda et al ( , 2016b; Tulasi Ram et al 2012; "Equatorial Atmosphere Radar (EAR) and ionosondes (CPN, KTB)" and "Case study: 27 March 2006, " and additional references in Tsunoda (2015)].…”
Section: Upwellings Can Have Modulation Depths Comparablementioning
confidence: 99%
“…6. There is mounting evidence that EPBs develop where there are pre-existing upwellings (LSWS) [e.g., Tsunoda and White (1981); Kelley et al (1981); Singh et al (1997); Eccles (2004); Fukao et al (2006); Thampi et al (2009); Tsunoda et al (2011Tsunoda et al ( , 2016aTsunoda et al ( , 2016b; Tulasi Ram et al 2012; "Equatorial Atmosphere Radar (EAR) and ionosondes (CPN, KTB)" and "Case study: 27 March 2006, " and additional references in Tsunoda (2015)].…”
Section: Upwellings Can Have Modulation Depths Comparablementioning
confidence: 99%
“…On 14–17 April 2011, eastward intrusion of DOAs associated with the sunset effect (Maruyama & Kawamura, ; Tsunoda et al, ) was seen around 10 UT. According to Tsunoda et al (), it is considered to be due to a strong postsunset rise of the ionosphere around the day‐night boundary near the magnetic equator slightly to the east of the great‐circle propagation path. In the dayside (before 10 UT), the Radio Australia signals were received at the azimuth angle around the great circle direction.…”
Section: Hf‐tep Experimentsmentioning
confidence: 99%
“…Recently, Tsunoda et al (, ) analyzed DOAs of OGCP of HF radio waves together with ionosonde measurements between the transmitter and receiver and showed that they could be classified into two groups, discrete and diffuse types. They concluded that the discrete‐type OGCP was due to multiple reflections of HF radio waves by unstructured upwellings associated with plasma bubbles, while the diffuse‐type OGCP was due to reflection from plasma structure in plasma bubbles.…”
Section: Introductionmentioning
confidence: 99%